Mono-energy coronary angiography with a compact light source - Eggl, Elena; Meehlem, Korbinian; Braig, Eva; Kulpe, Stephanie; Dierolf, Martin; Guenther, Benedikt; Achterhold, Klaus; Herzen, Julia; Gleich, Bernhard; Rummeny, Ernst; Noel, Peter B.; Pfeiffer, Franz; et al. (Progress in Biomedical Optics and Imaging - Proceedings of SPIE, 2017)
While conventional x-ray tube sources reliably provide high-power x-ray beams for everyday clinical practice, the broad spectra that are inherent to these sources compromise the diagnostic image quality. For a monochromatic x-ray source on the other hand, the x-ray energy can be adjusted to optimal conditions with respect to contrast and dose. However, large-scale synchrotron sources impose high spatial and financial demands, making them unsuitable for clinical practice. During the last decades, research has brought up compact synchrotron sources based on inverse Compton scattering, which deliver a highly brilliant, quasi-monochromatic, tunable x-ray beam, yet fitting into a standard laboratory. One application that could benefit from the invention of these sources in clinical practice is coronary angiography. Being an important and frequently applied diagnostic tool, a high number of complications in angiography, such as renal failure, allergic reaction, or hyperthyroidism, are caused by the large amount of iodine-based contrast agent that is required for achieving sufficient image contrast. Here we demonstrate monochromatic angiography of a porcine heart acquired at the MuCLS, the first compact synchrotron source. By means of a simulation, the CNR in a coronary angiography image achieved with the quasi-mono-energetic MuCLS spectrum is analyzed and compared to a conventional x-ray-tube spectrum. The results imply that the improved CNR achieved with a quasi-monochromatic spectrum can allow for a significant reduction of iodine contrast material.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Contrast agents; Coronary angiography; Inverse Compton X-rays; X-ray imaging